ANALISIS PENGARUH MOTIVASI TERHADAP KINERJA PETERNAK AYAM BROILER POLA KEMITRAAN (CONTRACT FARMING) DI KOTA PEKANBARU - Rasoki, Mai Yena Mawar; Cepriadi, Cepriadi; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aim to 1.)determine the level of motivation of plasma broiler breeders in partnership 2.)determine the level of peformance of plasma broiler breeders in partnership 3.) analyze the effect of motivation to plasma broiler breeders in partnership at Pekanbaru. This research using the secundary and the primary data, the secundary data is obtained by statistic center, the primary data is obtained by spreading questionaries to 40 respondent which are using random sampling technique. Then data analyze both qualitative and quantitative, qualitative data is the interpretation of the likert scale and the interpretation of the linear multiple regression by SPSS 17 include : coefficient of determination, F test, and T test.There are 9 motivation variable, the result of likert scale show the value of motivation is 3.40, it meants generally plasma breeders be criteria motivate. The value of peformance is 3.17, it meants that generally peformance of plasma breeders be criteria good enough. The result of multiple regression show that coefficient of determination is 0.545, it meants 54.5 percent motivation significant affecting peformance of plasma boriler breeders, while 45.5 percent remains is affect by another variabel beyond the equation model.Â Keywords: Broiler, Contract Farming, Motivation, Partnership And Peformance